The Spectrum of Neurological and White Matter Changes and Premutation Status Categories of Older Male Carriers of the FMR1 Alleles Are Linked to Genetic (CGG and FMR1 mRNA) and Cellular Stress (AMPK) Markers - Loesch, Danuta Z.; Trost, Nicholas; Bui, Minh Q.; Hammersley, Eleanor; Lay, Sui T.; Annesley, Sarah J.; Sanislav, Oana; Allan, Claire Y.; Tassone, Flora; Chen, Zhi-Ping; Ngoei, Kevin R. W.; Kemp, Bruce E.; et al. (Frontiers in Genetics, 2018)
The fragile X premutation (PM) allele contains a CGG expansion of 55-200 repeats in the FMR1 gene’s promoter. Male PM carriers have an elevated risk of developing neurological and psychiatric changes, including an approximately 50% risk of the Fragile X–Associated Tremor/Ataxia Syndrome (FXTAS). The aim of this study was to assess the relationships of regional white matter hyperintensities (wmhs) semi-quantitative scores, clinical status, motor (UPDRS, ICARS, Tremor) scales, and cognitive impairments, with FMR1-specific genetic changes, in a sample of 32 unselected male PM carriers aged 39-81 years. Half of these individuals were affected with FXTAS, while the non-FXTAS group comprised subcategories of non-affected individuals and individuals affected with non-syndromic changes. The dynamics of pathological processes at the cellular level relevant to the clinical status of PM carriers was investigated using the enzyme AMP-activated protein kinase (AMPK), which is a highly sensitive cellular stress-sensing alarm protein. This enzyme, as well as genetic markers – CGG repeat number and the levels of the FMR1 mRNA – were assessed in blood lymphoblasts. The results showed that the repeat distribution for FXTAS individuals peaked at 85-90 CGGs; non-FXTAS carriers were distributed within the lowest end of the PM repeat range, and non-syndromic carriers assumed an intermediate position. The size of the CGG expansion was significantly correlated, across all three categories, with infratentorial and total wmhs and with all motor scores, and the FMR1 mRNA levels with all the wmh scores, whilst AMPK activity showed considerable elevation in the non-FXTAS combined group, decreasing in the FXTAS group, proportionally to increasing severity of the wmhs and tremor/ataxia. We conclude that the size of the CGG expansion relates to the risk for FXTAS, to severity of infratentorial wmhs lesions, and to all three motor scale scores. FMR1 mRNA shows a strong association with the extent of wmhs, which is the most sensitive marker of the pathological process. However, the AMPK activity findings - suggestive of a role of this enzyme in the risk of FXTAS - need to be verified and expanded in future studies using larger samples and longitudinal assessment.